2016
DOI: 10.1007/s11064-016-1926-9
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Protected Neural Cells Against Aluminum-Maltolate-Induced Apoptosis by Preventing miR-19 Downregulation

Abstract: Aluminum (Al)-induced apoptosis is considered as the major cause of its neurotoxicity. Folic acid possesses neuroprotective function by preventing neural cell apoptosis. microRNAs (miRNAs) are important regulators of gene expression participating in cellular processes. As a key component of the miR-17-92 cluster, miR-19 is implicated in regulating apoptotic process, while its role in the neuroprotective effect of folic acid has not been investigated. The present study aimed to investigate the potential involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…When we compared the most significant up- or downregulated genes, we observed that most of the genes related to apoptosis ( TP53BP2, CSRNP1, TEAD, CDCA7, PPP1R15A ) were upregulated in Vac- or Adj-injected sheep. This is in agreement with other studies, in which aluminum-induced apoptosis in the human neuroblastoma cell line ( 58 ) and the expression of pro-apoptotic genes in human brain cells ( 55 ) were also found. In addition, some genes related to the immune response ( SKAP2, IGSF6, LST1, FGR, MAPK13 ), inflammatory response ( S100A12, ADGRE3, TREM1, STEAP4, NR4A3 ), cell growth ( HGF, CSF3R ), and cell-cell signaling ( AREG ) were upregulated in Vac-injected sheep but were downregulated in Adj-injected animals.…”
Section: Discussionsupporting
confidence: 93%
“…When we compared the most significant up- or downregulated genes, we observed that most of the genes related to apoptosis ( TP53BP2, CSRNP1, TEAD, CDCA7, PPP1R15A ) were upregulated in Vac- or Adj-injected sheep. This is in agreement with other studies, in which aluminum-induced apoptosis in the human neuroblastoma cell line ( 58 ) and the expression of pro-apoptotic genes in human brain cells ( 55 ) were also found. In addition, some genes related to the immune response ( SKAP2, IGSF6, LST1, FGR, MAPK13 ), inflammatory response ( S100A12, ADGRE3, TREM1, STEAP4, NR4A3 ), cell growth ( HGF, CSF3R ), and cell-cell signaling ( AREG ) were upregulated in Vac-injected sheep but were downregulated in Adj-injected animals.…”
Section: Discussionsupporting
confidence: 93%
“…Bcl-2 to play the antiapoptosis role, but also block the release of cyt-c to initiate the antiapoptosis mechanism, thereby protecting neurons against ischemic injury (Choi, Lee, Hong, & Lee, 2004;Liu et al, 2010). Moreover, Zhu et al (2016) found that miR-19b…”
Section: Discussionmentioning
confidence: 99%
“…Effects of Vitamin E (alpha-tocopherol and the water-soluble analog Trolox) were assessed in comparison to other antioxidant agents of alimentary origin, in order to test their action specificity. In particular, for our experiments we specifically selected: beta-carotene (21, 22), lycopene (22, 23), lutein (24), folic acid (25), ascorbic acid/Vitamin C (26), retinol/Vitamin A (27), Vitamin K1/phylloquinone, and Vitamin K2/menaquinones (28, 29).…”
Section: Methodsmentioning
confidence: 99%
“…For acute treatment, a single slice was incubated, from 40 min before HFS induction and for the duration of the whole experiment (about 1 h), in a bath solution containing the drug dissolved in Krebs' solution. Selected compounds were used in bath at the respective dose of: alpha-tocopherol = 100 μM and Trolox = 100 μM (9); beta-carotene = 100 μM (30); lutein = 20 μM (24); lycopene = 5 μM (22, 23); folic acid = 100 μM (25); Vitamin A = 1 μM (27); Vitamin C = 1–3 mM (26); Vitamin K1 = 20 μM, and Vitamin K2 = 10 μM (28, 29).…”
Section: Methodsmentioning
confidence: 99%